Tuberculosis and Granulomatosis with Polyangiitis: A Rare Overlap (Sir Salimullah Medical College Journal, 2026)
Bangladesh, a high tuberculosis (TB) burden country, frequently faces diagnostic challenges due to the protean manifestations of TB. Granulomatosis with polyangiitis (GPA), an ANCA-associated vasculitis, can closely mimic TB in clinical and radiological features, and very rarely the two may coexist. We report a 47-year-old male with fever, weight loss, respiratory distress, and mediastinal mass initially treated as TB. Subsequent deterioration with renal involvement, c-ANCA positivity, and hematuria suggested GPA. Immunohistochemistry of the mediastinal biopsy confirmed mycobacterial antigen, supporting concomitant TB. The patient required intensive care with anemia correction, antibiotics, and heart failure management. Following stabilization, he was treated with methylprednisolone and rituximab for GPA alongside a modified anti-TB regimen, which was well tolerated. His renal function and lung status improved significantly, and he was discharged on maintenance immunosuppression and anti-TB therapy. This case highlights the critical importance of considering dual pathology, as timely recognition and combined therapy can be lifesaving.Sir Salimullah Med Coll J 2025; 33: 135-139